A Summary of National Oceanic and Atmospheric Administration Space Weather Prediction Center Proton Event Forecast Performance and Skill - H. M. Bain; R. A. Steenburgh; T. G. Onsager; E. M. Stitely (Space Weather)
Abstract The effects of solar radiation storms at Earth are felt across a number of technology‐based industries. Energetic particles present during these storms impact electrical components on spacecraft, disrupt high frequency radio communications, and pose a radiation risk for passengers and crew on polar flight routes, as well as for astronauts. An essential aspect of space weather forecasting is therefore to predict the occurrence and properties of a solar proton event before it occurs. In this study, we review radiation storm products issued by the National Oceanic and Atmospheric Administration's Space Weather Prediction Center (SWPC) during Solar Cycles 23 and 24. These include three‐day probabilistic proton event forecasts and short‐term Warning and Alert hazard products. We present performance metrics and forecast skill scores for SWPC probabilistic forecasts and Warning products, which can be used as a benchmark for assessing the performance of radiation storm forecast models.